A Study of Secure Data Storage Analysis in Cloud Computing - Bunkar, Rajesh Kumar; Mishra, Dr Bharat; Rai, Dr. P.K (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud computing is an identical IT capacity (services, software, or infrastructure) delivered via internettechnologies in a pay-per-use, self-service way. Cloud storage based file management services, such as DropBox,Google Drive, OneDrive and Mega, are worldwide resource used by millions of users. Features for rising of outerfile systems with DropBox, FTP and GoogleDrive facilitate users have all their file sync and distribute tools in asingle interface. Cloud storage like DropBox, Google Drive, OneDrive and Mega Cloud to trust our data on otherpeople's data centre. OwnCloud is open source file sync and share can keep our data on our servers and decidewhat other public cloud services we want to integrate into personal cloud of cloud storage size, security, and usedin platform between online public cloud as OneDrive, GoogleDrive, DropBox, Mega, and private cloud storageOwnCloud with public cloud OpenShift and some file related storage analysis between them.